PERAN MAHASISWA DALAM MENGEMBANGKAN EDUKASI AGAMA ISLAM DENGAN PESANTREN KILAT ONLINE PADA LINGKUNGAN MASYARAKAT RUNGKUT - Christian Starly; Nalendra Fadila Saskara; Riki Audy Bin Ghozali; Muhammad Fawwaz Dhiaulhaq Hud (Jurnal Binagogik, 2024)
Pesantren is the oldest Islamic Education Institution in Indonesia that aims to spread and develop theteachings of Islam. In this modern era, online flash pesantren emerged as an innovation to offer flexibleand widely accessible religious learning utilizing technology, with the aim of fostering Islamicspirituality, educating mental and independence, and increasing participants' spiritual intelligence. Theonline flash Islamic boarding school is an innovation in Islamic religious education that offers flexibleand widely accessible learning by utilizing technology. This research examines the vital role of studentsin developing Islamic religious education through online flash pesantren. With access to technology anda high spirit of da'wah, students are able to create innovative learning media such as videos, applications,and online platforms. The online flash pesantren program is designed with a curriculum that coversimportant topics of Islam, varied teaching methods, and involves competent teachers and facilitators.Interviews with students of religious organizations revealed the importance of setting goals, objectives,effective promotion strategies, and continuous evaluation for program success. Online flash boardingschools have the potential to increase religious knowledge, shape character, and facilitate constructive online social interactions among participants. By utilizing technology, the program can reach a widerange of people and contribute to the development of Islamic religious education in the modern era. Therole of students is crucial in developing religious education through online flash pesantren by creatinginnovative learning media. Appropriate strategies and continuous evaluation are needed to ensure thesuccess of the program in strengthening Islamic values in the community.